(untitled) (Fiep Bulletin - online, 2011)
This study focuses on research environmental responsibilities represented among hikers, trekking practitioners of a Geopark. We chose as the site being investigated the Parque Natural Municipal de Nova Iguaçu (PNMNI), being the first Geopark in the State of Rio de Janeiro and so we seek to describe an investigate through statements from four hikers. In this unit, their environmental responsibilities with the local knowing how well they represent it. The Geopark (PNMNI) is constituted by a field of social environmental construction of citizenship where we investigate how the hikers appropriate the trails and ways existent there and as reevaluated. The strategies of knowledge production have used as four individual interviews with hikers, study participants and writing of the diary. We design looks on a symbolic mapping of the Geopark , how are produced the images of roads, trails, and how they are achieved and are visualized as the processes of the subjectivity of those actors, besides the possible environmental impacts caused by them. We can affirm that the discourses of these actors in the context social environment of Geopark in issue structure representations contributing to this positive development and make possible a construction of positive exercise ECOSOPHIC that Guattari (1990) specifies to be an ethical-political between three ecological records (environmental, social relations and human subjectivity), that space close to nature. The methodology enables us to overcome the physical dimension and makes the Geopark marked by new rationales and emotions of their users, the poeticization of its functionality subjectifivized by notions biocentrics.